2015
DOI: 10.1017/s1751731115001020
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the orexin system in the porcine uterus, conceptus and trophoblast during early pregnancy

Abstract: Orexin A and B are hypothalamic peptides derived from the prepro-orexin (PPO) precursor. Orexins stimulate food intake and arousal. Those peptides bind and activate two G protein-coupled receptors: orexin receptor 1 (OX1R) and orexin receptor 2 (OX2R). Numerous authors have suggested that orexins play an important role in the regulation of the reproductive functions. The objective of the present study was to analyse the presence of and changes in the gene and protein expression pattern of the orexin system in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 27 publications
(37 reference statements)
0
18
0
Order By: Relevance
“…The expression of the PPO gene, OXA and OXB proteins and OX1R and OX2R genes and proteins in the uterus during the oestrous cycle and early pregnancy has been previously reported [ 13 , 14 ]. The orexin system has been localised in the porcine uterus, however, there is a general scarcity of data describing the relationship between orexins and the factors regulating reproductive function, including steroid hormones and prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of the PPO gene, OXA and OXB proteins and OX1R and OX2R genes and proteins in the uterus during the oestrous cycle and early pregnancy has been previously reported [ 13 , 14 ]. The orexin system has been localised in the porcine uterus, however, there is a general scarcity of data describing the relationship between orexins and the factors regulating reproductive function, including steroid hormones and prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…Orexins participate in the regulation of reproductive function by influencing the hypothalamic-pituitary-ovarian axis. Our previous findings [ 13 , 14 ] indicate that the orexin system is expressed in the porcine uterus and is dependent on the local hormonal milieu. Progesterone could be responsible for the local regulation of orexin activity during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of orexins in the uterus has not been fully elucidated to date. Smolinska et al (2015) observed the expression of PPO, OX1R, OX2R genes and OXA, OXB, OX1R, OX2R proteins in the porcine endometrium, myometrium, conceptus, and trophoblast in the early stages of gestation. Orexin A was also found in human, canine, and feline placenta (Nakabayashi et al, 2003;Dall'Aglio et al, 2012, whereas OX1R was localized in the syncytiotrophoblast and decidual cells of feline placenta and OX2R was identified in human endometrial glands (Dall'Aglio et al, 2012).…”
Section: Introductionmentioning
confidence: 88%
“…In addition, LE cells differentiate from GE by the expression of genes like CYP26A1, that encodes a key enzyme of trans retinoic acid inactivation, already shown as strongly expressed in luminal epithelial cells of rat endometrium and playing a role in embryo implantation [44]. Endometrial expression of HCTR1 has been reported to be, with its main ligand orexin-A, an important local regulator of endometrial functions in porcine uterus [45,46].…”
Section: Transcriptome Of the Three Endometrial Cell Typesmentioning
confidence: 99%